BEYOND THE EXHIBITION: REFRAMING VISITOR ORIENTATION, SOCIAL INNOVATION, AND SOCIAL PERFORMANCE IN MUSEUMS THROUGH SME ENGAGEMENT - Rizal Hari Magnadi (International Journal of Small and Medium Enterprises and Business Sustainability, 2025)
This article examines how museums are redefining their role as public institutions by engaging small and medium enterprises (SMEs) as non-traditional visitors, co-creators, and innovation partners. Drawing on nonprofit marketing and market orientation literature, it argues that visitor orientation must expand beyond passive audience models to recognise SMEs as active stakeholders in cultural production and knowledge exchange. Methodologically, the study adopts a comparative qualitative multiple-case design across six public museums in Indonesia, purposively selected by institutional level (provincial vs city/town) and collection focus (cultural-historical vs generalist). Data are generated through semi-structured interviews with museum staff/leaders, SME partners, and relevant local government stakeholders, complemented by document analysis and (where feasible) field observations. Analysis uses NVivo-supported a priori thematic coding to build an analytical framework around three guiding codes: (1) visitor orientation towards SMEs, (2) museum-facilitated social innovation, and (3) museum social performance (outcomes and accountability). Findings show that museum social innovation increasingly emerges through co-created economic and cultural initiatives with heritage-based SMEs, producing hybrid value such as community entrepreneurship, identity-driven product development, and inclusive local branding. The study also argues that museum social performance should be assessed not only through access and participation metrics, but through ethical governance, benefit-sharing, and contributions to local creative ecosystems; academically, it advances theory on visitor orientation and multi-stakeholder public value, and practically, it offers actionable guidance for museums, policymakers, and cultural funders to design and evaluate stronger museum–SME collaborations for inclusive cultural development.